DNA damage responses by human ELG1 in S phase are important to maintain genomic integrity - Sikdar, Nilabja (2009)
Genomic integrity depends on DNA replication, recombination and repair, particularly in S phase. We demonstrate that a human homologue of yeast Elg1 plays an important role in S phase to preserve genomic stability. The level of ELG1 is induced during recovery from a variety of DNA damage. In response to DNA damage, ELG1 forms distinct foci at stalled DNA replication forks that are different from DNA double strand break foci. Targeted gene knockdown of ELG1 resulted in spontaneous foci formation of γ-H2AX, 53BP1 and phosphorylated-ATM that mark chromosomal breaks. Abnormal chromosomes including fusions, inversions and hypersensitivity to DNA damaging agents were also observed in cells expressing low level of ELG1 by targeted gene knockdown. Knockdown of ELG1 by siRNA reduced homologous recombination frequency in the I-SceI induced double strand break-dependent assay. In contrast, spontaneous homologous recombination frequency and sister chromatin exchange rate were upregulated when ELG1 was silenced by shRNA. Taken together, we propose that ELG1 would be a new member of proteins involved in maintenance of genomic integrity.